2000
DOI: 10.1016/s0091-3057(00)00223-9
|View full text |Cite
|
Sign up to set email alerts
|

The Delayed Effects of DTG and MK-801 on Latent Inhibition in a Conditioned Taste-Aversion Paradigm

Abstract: . The delayed effects of DTG and MK-801 on latent inhibition in a conditioned taste-aversion paradigm. PHARMACOL BIOCHEM BEHAV 66 (3) 533-539, 2000.-The delayed effects of phencyclidine (PCP) have been shown to disrupt latent inhibition (LI) in a conditioned taste-aversion paradigm. In an attempt to understand the mechanism of this disruption, the delayed effects of the selective sigma receptor agonist 1,3-Di(2-tolyl)guanidine (DTG) and the selective NMDA receptor antagonist MK-801 on latent inhibition were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 70 publications
5
8
0
Order By: Relevance
“…This result is consistent with two previous studies showing that ketamine or MK-801, injected before or just after preexposure, disrupted latent inhibition in a conditioned tasteaversion paradigm whereas no effect was obtained when these compounds were injected only at the conditioning stage (Aguado et al, 1994;Traverso et al, 2003). Several studies have failed however to find any disruption of latent inhibition after acute injection of noncompetitive NMDA antagonists (Moser et al, 2000) or reported abolition of latent inhibition with concomitant decrease in the conditioned response in control groups (Turgeon et al, 2000). Moreover, a recent study has shown that MK-801 induced, on the contrary, a persistent latent inhibition in a conditioned emotional response procedure when it was administered at the conditioning stage but not at the pre-exposure stage (Gaisler-Salomon and Weiner, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with two previous studies showing that ketamine or MK-801, injected before or just after preexposure, disrupted latent inhibition in a conditioned tasteaversion paradigm whereas no effect was obtained when these compounds were injected only at the conditioning stage (Aguado et al, 1994;Traverso et al, 2003). Several studies have failed however to find any disruption of latent inhibition after acute injection of noncompetitive NMDA antagonists (Moser et al, 2000) or reported abolition of latent inhibition with concomitant decrease in the conditioned response in control groups (Turgeon et al, 2000). Moreover, a recent study has shown that MK-801 induced, on the contrary, a persistent latent inhibition in a conditioned emotional response procedure when it was administered at the conditioning stage but not at the pre-exposure stage (Gaisler-Salomon and Weiner, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Experiment 1 showed that under conditions which led to LI in controls (40 pre-exposures and two conditioning trials), MK-801-treated rats showed intact LI, in line with previous studies in which NMDA antagonists administered at a low dose range spared LI (Weiner and Feldon 1992;Robinson et al 1993;Aguado et al 1994;Turgeon et al 1998Turgeon et al , 2000. Furthermore, experiment 2 showed that at this same dose, MK-801 led to the emergence of LI under conditions that disrupted LI in controls (40 preexposures and five conditioning trials), and this was replicated in the next three experiments.…”
Section: Discussionsupporting
confidence: 82%
“…Studies testing the effects of acute systemic administration of non-competitive NMDA receptor antagonists on LI reported that PCP, ketamine, and the more potent and selective NMDA antagonist MK-801 spared LI (Weiner and Feldon 1992;Robinson et al 1993;Aguado et al 1994;Turgeon et al 1998Turgeon et al , 2000; although at high doses, PCP and MK-801 given 20 h before the LI procedure disrupted LI in conditioned taste aversion; Turgeon et al 1998Turgeon et al , 2000. Likewise, MK-801 infusion into the dorsal hippocampus left LI intact (Zhang et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike amphetamine, acute administration of low-dose NMDA antagonists spares LI under conditions yielding LI in nontreated controls (Weiner and Feldon 1992;Aguado et al 1994;Klamer et al 2004;Palsson et al 2005;Robinson et al 1993;Turgeon et al 1998Turgeon et al , 2000 and in fact, produce an opposite behavioral effect on LI from that of amphetamine, namely, an abnormally persistent LI, that becomes manifested under conditions that prevent the expression of LI in no-drug controls (Gaisler-Salomon and Weiner 2003;Gaisler-Salomon et al 2008;Lipina et al 2005). This MK-801-induced attentional perseveration is reversed by atypical (clozapine and risperidone) but not typical (haloperidol) antipsychotic drugs (Gaisler-Salomon and Weiner 2003;Gaisler-Salomon et al 2008).…”
Section: Introductionmentioning
confidence: 99%